Sikap Konsumen dan Willingness to Pay (WTP) Pada Produk Buavita Royale: Consumer Attitude and Willingness to Pay (WTP) in Buavita Royale Products - Sugiyanthi, Diana; Nurmalina, Rita; Novianti, Tanti (Jurnal Aplikasi Bisnis dan Manajemen, 2020)
This study aims to determine consumer attitudes towards Buavita Royale products, analyze the factors that influence willingness to buy consumer (WTB), and measure the maximum value of willingness to pay consumers’ (WTP) towards Buavita Royale products. The results of research on consumer attitudes toward Buavita Royale products using the Fishbein analysis method found that overall obtained an assessment of 291.37 so that consumers remain willing to consume, buy and have the desire to pay for Buavita Royale products. Based on the research results of consumer attitudes with the Importance Performance Analysis (IPA) approach to find out what strategies can be carried out by the company is found packaging design variables, benefits, tastes, consumer experience and reputation of PT Unilever needs to be maintained, but the variables; recognition of product brands, availability in the market, and outstanding prices need to be improved. Factors that influence willingness to buy consumers’Buavita Royale products found that the variable that has a significant effect on consumers’ desire to pay for Buavita Royale products is that the prices of products circulating in the market today are not a problem for respondents, so product prices tend to increase consumers’ willingness to buy. Consumers also have a positive attitude towards Buavita Royale products. The maximum value of the consumer’s WTP against Buavita Royale products for 250 ml size with an average value of maximum price of Rp8,226 while for the size of 1000 ml consumers are willing to pay the maximum price with an average price of Rp30,019. Keywords: fishbein, IPA, consumer attitudes, willingness to pay, willingness to buy